2020
DOI: 10.1021/acsnano.9b06453
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Assembled α-Synuclein Nanoscavenger for Parkinson’s Disease

Abstract: Although emerging evidence suggests that the pathogenesis of Parkinson’s disease (PD) is closely related to the aggregation of alpha-synuclein (α-syn) in the midbrain, the clearance of α-syn remains an unmet clinical need. Here, we develop a simple and efficient strategy for fabricating the α-syn nanoscavenger for PD via a reprecipitation self-assembly procedure. The curcumin analogue-based nanoscavenger (NanoCA) is engineered to be capable of a controlled-release property to stimulate nuclear translocation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 73 publications
0
62
0
Order By: Relevance
“…[ 17,18 ] Appropriation of brain‐targeting ligands, such as transferrin receptors and glucose transporters, facilitates BBB penetration by nanodelivery systems for more effective neurodegenerative diseases therapy. [ 19,20 ] Although several systems have been established to delivery nanomedicines that target α ‐synuclein, as another pathological hallmark in PD progression, [ 20,21 ] targeted delivery systems to treat PD by restoring DA activity remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,18 ] Appropriation of brain‐targeting ligands, such as transferrin receptors and glucose transporters, facilitates BBB penetration by nanodelivery systems for more effective neurodegenerative diseases therapy. [ 19,20 ] Although several systems have been established to delivery nanomedicines that target α ‐synuclein, as another pathological hallmark in PD progression, [ 20,21 ] targeted delivery systems to treat PD by restoring DA activity remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al developed an intranasal delivery system for the brain-targeted delivery of a curcumin analogue-based nanoscavenger (curcumin analogue molecules with polyethylene glycol). The authors showed that this treatment stimulated nuclear translocation of transcription factor EB, one of the major autophagy regulators, thereby triggering both autophagy and calcium-dependent exosome secretion for the clearance of α-Syn [66]. Finally, chronic and acute curcumin treatment of transgenic mice overexpressing GFP-tagged wild-type α-Syn improved motor behavior, which was correlated with an increase in phosphorylated α-Syn protein in the cortical presynaptic terminals [67].…”
Section: Parkinson's Diseasementioning
confidence: 97%
“…It has been demonstrated that curcumin regulates the early aggregation phases of reduced superoxide dismutase 1 (SOD1), one of the main proteins associated with Amyotrophic Lateral Sclerosis (ALS), leading to the production of non-fibrillar smaller and less toxic aggregates [66]. It also binds these products strongly, blocking their aggregation sites and, thus, inhibits the production of toxic species [68].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Various nanomedicine strategies, such as solid lipid nanoparticles, polymeric micelles, nano-emulsions and nanosuspensions/nanocrystals, have been recently exploited for effectively circumventing the delivery limitations of curcumin. [128][129][130] For instance, curcumin encapsulated in poly (lactic-coglycolic acid) nanoparticles not only offers significantly better BBB penetration in rat models but also shows longer retained time in the cerebral cortex and hippocampus when compared with that of curcumin molecules. 131 Besides, He et al 132 applied solid lipid nanoparticles to co-load HU-211 and curcumin that can deliver more curcumin to the brain and increase the neurotransmitter level in brain tissue.…”
Section: Ongoing Challenges Of Curcumin In Antidepressant Treatmentsmentioning
confidence: 99%